Mapping the Research in Environmental and Sustainability Education in Teacher Education in Canada - Kennedy, Alysse; Inwood, Hilary; Villemagne, Carine (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2025)
This article examines the evolving landscape of environmental and sustainability education in teacher education (ESE-TE) in Canada through a scoping review of 198 peer-reviewed studies published between 2005 and 2020. Situated within broader international efforts to reorient education toward sustainability, the review maps the theoretical, methodological, and linguistic contours of ESE-TE scholarship across the country. Findings reveal a field characterized predominantly by qualitative research, strong representation from Ontario-based scholars, and limited contributions in French and from northern regions. The increasing integration of Indigenous education and land-based learning signals a promising yet complex engagement with decolonizing approaches to sustainability. However, significant gaps persist in the inclusion of diverse epistemologies, methodological breadth, and Indigenous-led scholarship. By tracing these developments, this study contributes to ongoing conversations about how Canadian faculties of education might mobilize research and collaboration to address the climate crisis and advance the transformative aims of sustainability education.